Penggunaan Media Video dalam Pembelajaran Daring Mata Pelajaran IPA Kelas V SD - Monika, Linda Tria; Tisngati, Urip; Setyawati, Erna (PGSD STKIP PGRI Pacitan, 2021)
The purpose of this study was to describe: (1) the procedure for using video media in online learning for science subjects for class V SD Negeri 1 Hadiwarno, (2) the barriers for teachers and students in using video media in online learning for science subjects for class V SD Negeri 1 Hadiwarno , (3) the efforts of teachers and students to face obstacles in using video media in online learning for fifth-grade science subjects at SD Negeri 1 Hadiwarno. Qualitative research was used in this study. A teacher and 13 fifth grade students of SD Negeri 1 Hadiwarno as subjects were selected by purposive sampling technique. The technique of observation, interviews and documentation on the use of video media in online learning of science subjects was chosen as the data collection method.. The findings of this study are: (1) the use of video media in online learning for science subjects class V SD Negeri 1 Hadiwarno was categorized as good, the implementation was by existing procedures; (2) the barriers experienced by teachers and students included difficult internet signal and expensive internet quota fees; (3) the efforts made by teachers and students to face these obstacles are suggestions for using hotspots from parents' cellphones, looking for wifi to the homes of friends and closest neighbours, thus helping smoothness in participating in online learning.